The church awakening : an urgent call for renewal - Swindoll, Charles R. (New York : FaithWords, 2010)
Charles Swindoll discusses the challenges, struggles, and priorities of the church in the twenty-first century. He reveals the problems inherent in the entertainment-based postmodern church and shows how a return to biblical teaching will restore its strength and impact. --from publisher description.
The church : let's start here -- Challenges, struggles, solutions, priorities -- Distinctives of a contagious church -- Worship : a commitment -- not a war -- What must the church realize? -- How should the church react? -- The church on a long drift -- It's time to "restore the years."
Includes bibliographical references (pages 273-282).
Keywords: Church renewal